A Retrospective Analysis of Antithrombin III Replacement Therapy for the Treatment of Hepatic Sinusoidal Obstruction Syndrome in Children Following Hematopoietic Stem Cell Transplantation. Issue 2 (March 2020) - Kim, Miriam; Rao, Seema; Eickhoff, Jens C.; DeSantes, Kenneth B.; Capitini, Christian M.
Abstract : Hepatic sinusoidal obstruction syndrome (SOS) remains a serious complication of hematopoietic stem cell transplantation (HSCT). In this single institution retrospective case series, 18 children developed SOS after HSCT. Patients were treated with antithrombin III (ATIII), defibrotide, or ATIII followed by defibrotide. Twelve of 13 patients who were treated with ATIII therapy alone had complete resolution of SOS, including 4 of 5 children with severe SOS. In this limited cohort, ATIII was safe and successfully prevented progression of hepatic SOS following HSCT in the majority of children at our center.